2020
DOI: 10.17516/1997-1370-0660
|View full text |Cite
|
Sign up to set email alerts
|

Specifics of the Attitude of Students with Deviant Behaviour to School Mediation Service

Abstract: This article discusses the perception of the effectiveness of school mediation services by adolescents with deviant behaviour. The research was based on Russian speaking adolescents aged 13-17 years (128 interviewees, including 78 girls and 50 boys). The questionnaire was developed in compliance with similar researches using expert evaluation. The results of the research are analyzed as per the Pearson correlation coefficient. The analysis of the difference in the perception of the effectiveness of mediation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Regarding the objective of gaining a deeper understanding of the main differences between peer mediators and non-mediators, it has been demonstrated that mediators show more positive opinions. This situation is understandable since those who have first-hand experience in school mediation are more capable of detecting its educational potential, as shown in other studies (Andronnikova, Radzikhovskaya, 2020;Hansberry, Hansberry, 2018). Undoubtedly, mediation provides valuable lessons for being a decent person and living with others; in the case of mediators, it also provides practical tools that strengthen these skills beyond the school setting.…”
Section: Discussionmentioning
confidence: 71%
“…Regarding the objective of gaining a deeper understanding of the main differences between peer mediators and non-mediators, it has been demonstrated that mediators show more positive opinions. This situation is understandable since those who have first-hand experience in school mediation are more capable of detecting its educational potential, as shown in other studies (Andronnikova, Radzikhovskaya, 2020;Hansberry, Hansberry, 2018). Undoubtedly, mediation provides valuable lessons for being a decent person and living with others; in the case of mediators, it also provides practical tools that strengthen these skills beyond the school setting.…”
Section: Discussionmentioning
confidence: 71%